2014
DOI: 10.1038/srep05854
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Study on Children's Music Training Experience and Academic Development

Abstract: This study examined the relation between long-term music training and child development based on 250 Chinese elementary school students' academic development of first language (L1), second language (L2), and mathematics. We found that musician children outperformed non-musician children only on musical achievement and second language development. Additionally, although music training appeared to be correlated with children's final academic development of L1, L2, and mathematics, it did not independently contri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
2
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 38 publications
1
48
2
4
Order By: Relevance
“…With regard to first language skills, results of an RCT by Cogo-Moreira et al ( 2013 ) [21] showed positive growing slopes in Portuguese language in the children who completed a 5-month music education program in comparison to the control children. Findings were in contrast to the results of Yang et al ( 2014 ) [43] who, using a non-randomized, longitudinal design, examined the relation between long-term music training and, among other skills, academic development of Chinese language among 250 Chinese elementary school students (mean age 78 months). Children who took part in formal music training out of school around the beginning of semester three, were categorized as musician children ( n = 77) whereas the remaining children, who had not received formal music training throughout this study, were categorized as non-musician children ( n = 173).…”
Section: Resultscontrasting
confidence: 99%
“…With regard to first language skills, results of an RCT by Cogo-Moreira et al ( 2013 ) [21] showed positive growing slopes in Portuguese language in the children who completed a 5-month music education program in comparison to the control children. Findings were in contrast to the results of Yang et al ( 2014 ) [43] who, using a non-randomized, longitudinal design, examined the relation between long-term music training and, among other skills, academic development of Chinese language among 250 Chinese elementary school students (mean age 78 months). Children who took part in formal music training out of school around the beginning of semester three, were categorized as musician children ( n = 77) whereas the remaining children, who had not received formal music training throughout this study, were categorized as non-musician children ( n = 173).…”
Section: Resultscontrasting
confidence: 99%
“…It is possible that the improvements in speech-in-noise perception observed in our study could result from participation in additional enrichment activities but not specifically from engagement with music, for example, as a result of additional linguistic interaction with teachers, mentors and fellow students in the course of musical training. A recent longitudinal study assessing the impact of music training on academic development failed to identify significant improvements beyond musical achievement and second language development, and encouraged caution in the interpretation of the non-musical cognitive benefits of music training [92]. However, previous cross-sectional studies indicate there may be specific links between music training and speech processing, for example demonstrating superior speech-in-noise abilities in musically-trained children compared with non-musician children matched for extra-curricular activities [58], and random-assignment longitudinal studies comparing music training with painting classes demonstrated enhanced speech processing only in the musically-trained group [48,65].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, music training is associated with L1 phonological perception (Zuk et al, 2013) and reading abilities (Corrigall & Trainor, 2011), and with L2 fluency (Swaminathan & Gopinath, 2013;Yang, Ma, Gong, Hu, & Yao, 2014). Longitudinal interventions with random assignment indicate that music training may actually cause improvement in children's speech perception (Degé & Schwarzer, 2011;Flaugnacco et al, 2015;François, Chobert, Besson, & Schön, 2013;Moreno et al, 2009;Thomson et al, 2013).…”
Section: Music Training and Speech Perceptionmentioning
confidence: 99%